2000
DOI: 10.3168/jds.s0022-0302(00)75116-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particle Size on the Effectiveness of the Fiber in Barley Silage

Abstract: We used eight multiparous Holstein cows in a 4 x 4 Latin square design to evaluate the effects and possible interactions between silage particle size and concentrate level on chewing activities and productivity of cows fed barley-based total mixed rations (TMR). Diets were designed with two forage-to-concentrate ratios (low forage, 45:55, high forage 55:45), combined with two theoretical chop lengths of barley silage (short = 4.68 mm and long = 18.75 mm). Diets were formulated to provide similar and above-mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
30
2
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 26 publications
11
30
2
7
Order By: Relevance
“…The most common reasons for the drop in rumen NH 3 concentration are explained by a reduction in the degradability of feed proteins. In our earlier experiment using barley silage with similar particle size, chewing activity was reduced when diets containing short barley silage were fed (Soita et al 2000). This may have decreased saliva production and therefore recycling of blood urea via the saliva; however, our results clearly show ammonia concentrations were above minimum requirements.…”
Section: Discussioncontrasting
confidence: 55%
“…The most common reasons for the drop in rumen NH 3 concentration are explained by a reduction in the degradability of feed proteins. In our earlier experiment using barley silage with similar particle size, chewing activity was reduced when diets containing short barley silage were fed (Soita et al 2000). This may have decreased saliva production and therefore recycling of blood urea via the saliva; however, our results clearly show ammonia concentrations were above minimum requirements.…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore, increased chewing activity in the fine corn silage diets (per kg peNDF) was due to more rumination on fine corn silage diets. But Soita et al (2000) reported that reducing corn silage particle size of 19 to 13 mm has little effect on chewing activity, but decreasing from 13 to 6 mm caused 30% of the chewing activity to decrease. It could be that part of the differences between hay in stimulating chewing activity was due to the differences in forage particle size, density and the physical interaction with other feeds in the rumen.…”
Section: Parametermentioning
confidence: 99%
“…Yansari et al (2004) found that reducing alfalfa hay particle size in cow diets of 19 to 10 and 2 mm, the time consumption declined per kg DM and NDF. Soita et al (2000) reported that comparison between four diets with two levels of particles size and two levels of concentrate particle size had a high significant effect on time consumption and time consumption per kg of forage and NDF intake. In the experiment of Schwab et al (2002), time consuming (minutes per day) and consumption (min) per kg DM and NDF intake did not decrease significantly in corn silage with size 18 mm vs. 32 mm; but differences were significant between diets containing corn silage with a theoretical cut length of 13 mm vs. 19-mm per kg DM.…”
Section: Parametermentioning
confidence: 99%
“…Variações na FDNfe de forragens vêm sendo avaliadas sobre as atividades de alimentação, ruminação, ócio e mastigação (De Boever et al, 1993a;De Boever et al, 1993b;Mooney & Allen, 1997;Clark & Armentano, 1999;Soita et al, 2000;Schwab et al, 2002), sendo que em três desses estudos ocorreu efeito da FDNfe da forragem sobre a atividade de mastigação (De Boever et al, 1993b;Mooney & Allen, 1997;Soita et al, 2000) porém nos demais a atividade de mastigação não foi alterada (De Boever et al, 1993a;Clark & Armentano, 1999;Schawb et al, 2002). Em outro estudo houve correlação significativa entre o teor de FDNfe da ração com as atividades de ruminação e mastigação (soma dos tempos entre alimentação e ruminação) mas não com a atividade de alimentação (Beauchemin et al, 2003).…”
Section: Introductionunclassified